PENERAPAN MODEL PEMBELAJARAN ROLE PLAYYING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI DI MAS AL IKHLAS - Idarianty, Idarianty; Fadilah, M Arifky; Suryani, Irma; Fajri, Nurman (Raudhah - Proud To Be Professional, 2024)
Role playing learning model or role playing is a learning method that involves students to play characters in everyday life. Learning using the role playing method can make students more active and creative in following lessons. The purpose of this study was to determine the application of the role playing learning model in increasing student learning motivation in PAI subjects at MAS Al Ikhlas. This research method uses a qualitative approach with content analysis. While the data collection is a literature review. The results of the study showed that the results of the initial observations conducted by the researcher showed that, as an initial step in implementing the role playing method, the researcher must know the previous method used by the teacher. The researcher conducted research in 2 classes, namely class X.1 as the Experimental class and class X.2 as the control class. The results of the observations conducted by the researcher were that class X.1 students had a low level of learning activity. where there are students who fall asleep during learning, there are students who are lazy during learning, there are students who are busy with their own affairs, and there are students who are busy chatting with their friends to the point of disrupting the learning conduciveness, The lowest student result before the treatment was 32, while the highest result was 43. After the treatment, students got the lowest score of 45 and the highest score of 57. The final result can be obtained that the experimental class using the role playing learning method got a higher average score of 80.25 than the control class using the lecture learning method, which was 72.15.